2023
DOI: 10.30574/wjarr.2023.19.3.1886
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lead ions from wastewater using raw and activated carbon of Pterocarpus santalinoides shell

Christopher C. Onyemenonu,
Leo C. Osuji,
Nnaemeka C. Ngobiri

Abstract: Removing toxic metals from the environment is a primary concern for researchers because of their hazardous effects. In this study, raw and activated Pterocarpus santalinoides shell was utilized in removal of lead (Pb) metal from an aqueous solution. The prepared adsorbents were analysed by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and mineral composition to identify their structural composition and understand the adsorption mechanism. The influence of various adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The significant changes were seen on the surfaces of this adsorbent after adsorption of Cd 2+ ions. These results revealed that raw and activated carbon derived from the Pterocarpus santalinoides fruit has enough active surface area and binding cavities to adsorb cadmium ions [16]. The result of the mineral content of the raw and activated carbon of Pterocarpus santalinoides fruit shows that sodium recorded the highest amount in both the raw (0.2577 mg/g) and activated carbon derived from fruit (0.2819 mg/g) while magnesium recorded the least value in raw (0.1997mg/g) and activated carbon (0.1720mg/g) as tabulated in Table 1.…”
Section: Characteristics Of the Adsorbentsmentioning
confidence: 85%
See 2 more Smart Citations
“…The significant changes were seen on the surfaces of this adsorbent after adsorption of Cd 2+ ions. These results revealed that raw and activated carbon derived from the Pterocarpus santalinoides fruit has enough active surface area and binding cavities to adsorb cadmium ions [16]. The result of the mineral content of the raw and activated carbon of Pterocarpus santalinoides fruit shows that sodium recorded the highest amount in both the raw (0.2577 mg/g) and activated carbon derived from fruit (0.2819 mg/g) while magnesium recorded the least value in raw (0.1997mg/g) and activated carbon (0.1720mg/g) as tabulated in Table 1.…”
Section: Characteristics Of the Adsorbentsmentioning
confidence: 85%
“…The adsorption percentage of Cd 2+ decreased from 99.79 to 80.57% and 99.40 to 81.76% for raw and activated carbon of Pterocarpus santalinoides fruit respectively. This trend is possible because the number of available adsorbent active sites is more when compared to the number of cadmium ion at lower concentration [16]. This result indicates that low adsorption percentage was recorded at high initial cadmium concentrations.…”
Section: Effect Of Initial Metal Concentrationmentioning
confidence: 87%
See 1 more Smart Citation